A retrospective study of 10 spontaneous cases of feline atopic dermatitis (1995-1997) - SARIDOMICHELAKIS (Μ. Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ten atopic cats (5 DSH, 4 Siamese, one Persian) were admitted to the Clinic of Companion Animal Medicine, Faculty of Veterinary Medicine, A.U.T., because of a seasonal (3/10) or nonseasonal (1/10) pruritic skin disease. The seasonal pattern of the clinical signs could not be established in the rest 6 cats. The presenting cutaneous syndromes were miliary dermatitis (6 cats), self- induced alopecia - hypotrichosis (5 cats), indolent ulcer (one cat), linear eosinophilic granuloma (one cat) and head and neck self - inflicted dermatitis (one cat), some appearing alone (5/10) or in various combinations (4/10). One cat had a generalized but non - lesionai pruritus. The onset of these manifestations ranged from 6 months to 8.5 years. The aeroallergens implicated by the ID skin test were Dermatophagoides farinae (9/10), D. pteronyssinus (4/10), Acarus siro (4/10), house dust, cottonseed and tree pollens (2/10) and grass and weed pollens (1/10). ID test reactions to single or multiple aeroallergens were detected in 2 and 8 cats, respectively. Although 5 of the 10 atopic cats also reacted positive to ID test with flea allergen, there was not strong evidence that flea allergic dermatitis had been coexisting in 4 of them. Other conditions associated (conjuctivitis, bronchial asthma) or not (otodectic otitis externa) with feline atopy were seen in 3 cats.